(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2019)
The present study aimed to measure the transformation of stimulus functions after performing a typical ACT exercise - the Leaves on a Stream metaphor. Nineteen adults participated in this study, a one-group pretest–posttest design. Experimental procedure: Phase 1: initial questionnaires; Phase 2: relational training (MTS) to establish two classes of equivalent stimuli, A1B1C1D1 and A2B2C2D2; Phase 3: aversive conditioning and teaching of avoidance responses (for A1) and approximation (for A2); Phase 4: Pre-test of transfer of functions (for C1 and C2) with binary measures (avoidance task and approximation) and continuous measures (various scales of self-reporting); Phase 5: (VI): Intervention (Metaphor Leaves on a Stream). Phase 6: Transfer of function post-test (see Phase 4). The comparison of the pre and post intervention results indicates subtle changes in the verbal report measures on the aversivity of stimuli. There was no effect on the avoidance response.